High Mass-Loading Sulfur-Composite Cathode for Lithium-Sulfur Batteries - Baikalov, Nurzhan; Serik, Nurassyl; Kalybekkyzy, Sandugash; Kurmanbayeva, Indira; Bakenov, Zhumabay; Mentbayeva, Almagul (Frontiers in Energy Research, 2020)
This research aimed to increase the mass loading of sulfur in the composite electrode in order to increase the energy density of the lithium-sulfur (Li-S) cell. This requires designing the electrode with the use of conductive agents to maintain the conductivity of the sulfur composite. Therefore, the composite of sulfur with polyacrylonitrile (PAN) and carbon nanotubes (CNT) was synthesized by heating. Following that, the mass loading of sulfur was increased by using several layers of carbon fiber paper (CFP) with a large free space as a three-dimensional current collector. As a result of the heat treatment and formation of covalent bonding between pyrolyzed PAN and sulfur, uniform distribution and enhanced conductivity were achieved, while CNT maintained structural integrity, acting as an interwoven network. Due to these advantages, the mass loading of sulfur was increased up to 5 mg cm–2 while maintaining a high initial specific capacity of 1400 mAh g–1 and stable cyclability.